Antimicrobial consumption in a hospital environment before and after restrictive commercialization measures in Brazil - Malta, Jessica Soares; Pádua, Cristiane Aparecida Menezes de; Cintra, Leandro Pinheiro; Machado, Carla Jorge; Costa, Josiane Moreira da; Ribeiro, Andréia Queiroz (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: The consumption of antimicrobials (ATB) has been described as one of the causes of Bacterial Resistance. In 2010, RDC 44 was published in Brazil, which restricts the free sale of ATB to reduce antimicrobial resistance in hospitals. Aim: to identify the consumption of ATB in a teaching hospital before and after the implementation of the restrictive measure on the commercialization of antimicrobials in Brazil. Outlining: Cross sectional study carried out in a general hospital. Analyzes were carried out in two phases, using the variables ATB consumption, expressed in defined daily dose (DDD), average use of different ATB per patient and the frequency of resistant microorganisms in the period. Results: The average use of ATB per patient was 2.56 (Standard Deviation (SD) ± 2.02) and2.40 (SD ± 1.89) in phases I and II, respectively (p=0.0007). The general variation in defined daily dose was 1.89%, however drugs with negative variation were observed. A higher frequency of resistant microorganisms isolated in phase I was observed compared to phase II (OR=1.48, CI: 1.13-1.93, respectively). Implications: A difference was identified in the consumption of ATB between the periods, with an increase in general consumption, in DDD, but a lower average number of different ATBs per patient and a lower occurrence of resistant microorganisms.